2019
DOI: 10.3389/fpls.2019.00643
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Ectomycorrhizal Fungal Communities and Exploration Types Relate to the Environment and Fine-Root Traits Across Interior Douglas-Fir Forests of Western Canada

Abstract: Large-scale studies that examine the responses of ectomycorrhizal fungi across biogeographic gradients are necessary to assess their role in mediating current and predicted future alterations in forest ecosystem processes. We assessed the extent of environmental filtering on interior Douglas-fir ( Pseudotsuga menziesii var. glauca (Beissn.) Franco) ectomycorrhizal fungal communities across regional gradients in precipitation, temperature, and soil fertility in inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 96 publications
(153 reference statements)
8
47
0
Order By: Relevance
“…However, a single measure of colonization rate may less relevant than ectomycorrhizal community composition in Douglas-fir forests [39] and may be more relevant in arbuscular mycorrhizal plant species [7,33]. In a complementary study across the same biogeographic gradient, we showed that root diameter was not related to patterns of ectomycorrhizal fungal exploration type (see [40]) and that fine roots with high RTD and low C:N were more frequently colonized by ectomycorrhizal fungi with short emanating hyphae [26]. Whether association with ectomycorrhizal fungi that proliferate short emanating hyphae could lead to increased acquisitive capacities of thick, large-diameter Douglas-fir fine roots requires further research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a single measure of colonization rate may less relevant than ectomycorrhizal community composition in Douglas-fir forests [39] and may be more relevant in arbuscular mycorrhizal plant species [7,33]. In a complementary study across the same biogeographic gradient, we showed that root diameter was not related to patterns of ectomycorrhizal fungal exploration type (see [40]) and that fine roots with high RTD and low C:N were more frequently colonized by ectomycorrhizal fungi with short emanating hyphae [26]. Whether association with ectomycorrhizal fungi that proliferate short emanating hyphae could lead to increased acquisitive capacities of thick, large-diameter Douglas-fir fine roots requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Two regions (Kamloops and Williams Lake) were in the Interior Douglas-fir biogeoclimatic zone (IDF) and three regions (Salmon Arm, Nelson, and Revelstoke) were in the Interior Cedar-Hemlock biogeoclimatic zone (ICH) [47]. Regions were distributed along substantial precipitation and temperature gradients (see Table 1 in [26]; Figure S3). Sites in Williams Lake had the lowest MAT (on average 3.4 °C) followed by Revelstoke, Kamloops, Salmon Arm and Nelson (on average 7.3 °C).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, trees in the oldest plots had lower genet colonization and growth compared to those in the younger plots (Table 1; Supporting Information : Table S1). A nearby study of EM fungi in British Columbia found divergent foraging strategies between EM fungi and fine roots (Defrenne et al., 2019). This provides further evidence to suggest that the Rhizopogon spp.…”
Section: Discussionmentioning
confidence: 99%